Internet of Things-Based Concrete Curing Invention for Construction Quality Control. (8th June 2021) - Lo, King-Chi; Kwok, Heung-Wing Terry; Siu, Ming-Fung Francis; Shen, Qiping Geoffrey; Lau, Chi-Keung
Abstract : The efficiency of the traditional concrete curing process on site is low, due to the difficulties in providing continuous supervision and control of the curing environment, leading to considerable variation in the curing regimes experienced by different concrete pours. To enhance concrete curing practice, technologies have been harnessed which eliminate human involvement enabling more rigorous control of the environmental conditions affecting curing, but the potential for Internet of Things (IoT) technologies had yet to be explored in this context. This research study examined an IoT-based concrete curing control system based on sensor technologies invented for monitoring and controlling the moisture content of hardening concrete to the levels appropriate for good quality hardened concrete. Based on on-site experiments, the performance of this IoT-based method was compared with the performance of traditional curing methods. The results indicate that the system invented outperforms the traditional approach both in terms of concrete curing quality and time spent on supervision.